2019
DOI: 10.1007/s10973-019-08715-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of barium oxide on glass-forming ability and glass stability of the tellurite–phosphate oxide glasses

Abstract: The effect of BaO content on the glass-forming ability, glass stability and structure of tellurite-phosphate oxide glasses in the 70TeO 2-10P 2 O 5-(20-x)ZnO-xBaO (x = 0, 5 and 10 mol%) system has been discussed. From the differential scanning calorimetry, the glass transition (Tg), crystallization (Tc) and the melting (Tm) temperatures were estimated. The decrease in reduced glass transition temperature (Tr g) and glass-forming tendency parameter (K h (Tc 1)) with addition and increasing BaO caused a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…Also, Aboutaleb et al 56 reported increasing T g with BaO doping in binary BaO–B 2 O 3 glasses. On the other hand, the present studies demonstrate the reducing T g with increasing BaO content for both the binary BaO–SiO 2 as well as quaternary Ba-NBS glasses, which is in good agreement with the earlier studies of Lesniak et al 54 Thus, the present results show that the addition of BaO in the glass matrix would facilitate the easier fabrication of glass by reducing the glass transition temperature.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Also, Aboutaleb et al 56 reported increasing T g with BaO doping in binary BaO–B 2 O 3 glasses. On the other hand, the present studies demonstrate the reducing T g with increasing BaO content for both the binary BaO–SiO 2 as well as quaternary Ba-NBS glasses, which is in good agreement with the earlier studies of Lesniak et al 54 Thus, the present results show that the addition of BaO in the glass matrix would facilitate the easier fabrication of glass by reducing the glass transition temperature.…”
Section: Resultssupporting
confidence: 93%
“…Notably, here, the oxygen atoms connected to either of Si/B on both the ends were considered as BO. The increasing NBOs with BaO doping suggest that Ba will break the random network of glass, similar as shown by the studies of Lesniak et al 54 In particular, small field strength and large ionic radius of barium ions result in a network modifier behavior; 56 therefore, the NBO fraction of the glass structure is increased with BaO doping. Further, for a similar concentration of BaO, the NBOs were detected to be higher for Ba-NBS (BS10) than BaO-SiO 2 (B10) due to the higher concentration of network modifiers (Na 2 O + BaO) for B10 than BS10.…”
Section: Msde Papersupporting
confidence: 79%
See 1 more Smart Citation
“…Figure 3 shows the normalized to the band at ~1030 cm −1 FTIR spectra (in the 1300–500 cm −1 range) of the precursor oxyfluoride phospho-tellurite glass with varying ErF 3 concentrations. As shown in Figure 3, all spectra presented the typical bands characteristic for tellurite glasses, i.e., at 610, 710, 770 cm −1 [58,59,60] and phosphate glasses, i.e., the bands at 500 cm −1 and in the 1300–900 cm −1 range [61,62,63,64,65,66,67].…”
Section: Resultsmentioning
confidence: 99%
“…Particularly noteworthy are the glass modifiers such as alkaline earth metal oxides (MO = MgO, CaO, SrO, BaO) that strongly influence the properties of glass systems [ 11 , 12 , 13 , 14 ]. Previously published results indicate that the depolymerization of the glass network due to the incorporation of alkaline earth oxides into the glass matrix promotes the formation of non-bridging oxygen (NBO) groups [ 15 ]. Moreover, Pavić et al [ 16 ] stated that modifiers like MgO, CaO as well as BaO influence some properties (electrical, dielectric and spectroscopic) of Fe 2 O 3 doped into phosphate glasses.…”
Section: Introductionmentioning
confidence: 99%